Strategic sophistication of individuals and teams in experimental normal-form games - Matthias Sutter; Simon Czermak; Francesco Feri (University of Innsbruck, Department of Public Finance, 2010)
We present an experiment on strategic thinking and behavior of individuals and teams in one-shot normal-form games. Besides making choices, decision makers have to state their first- and second-order beliefs. We find that teams play the Nash strategy significantly more often, and their choices are more often consistent by being a best reply to first order beliefs. We identify the complexity of a game and the payoffs in equilibrium as determining the likelihood of consistent behavior according to textbook rationality. Using a mixture model, the estimated probability to play strategically is 62% for teams, but only 40% for individuals.
Keywords: C72; C91; C92; 330; Strategic sophistication; beliefs; experiment; team decision making; individual decision making; Normalformspiel; Spieltheorie; Entscheidung; Gruppenentscheidung; Test; Schweden